PENGARUH PROFITABILITAS, LIKUIDITAS DAN MANAJEMEN ASET TERHADAP KINERJA PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Halim, Stephanie; Richandy, Grace; Panggabean, Dini Maulina (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study aims to analyze and determine the simultaneous and partial effects of Profitability, Liquidity, and Asset Management on Company Performance, with Firm Size as a moderating variable, in consumer cyclicals and consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 20212023 period. The research population consisted of 277 companies. The sampling method used was purposive sampling, resulting in a sample of 101 companies with 303 observation data points. Research data were obtained from the financial statements of consumer cyclicals and non-cyclicals companies listed on the IDX during the specified period. The data analysis methods included multiple linear regression and moderated regression analysis using the interaction test approach. The results of the analysis show that, simultaneously, Profitability, Liquidity, and Asset Management significantly affect Company Performance. Partially, Profitability and Liquidity have a positive and significant effect, while Asset Management has no significant effect on Company Performance. Furthermore, the Firm Size variable moderates the relationship between Profitability and Company Performance, but does not moderate the relationships between Liquidity or Asset Management and Company Performance